Assessing the Impact of CALGB 9343 on Surgical Trends in Elderly-Women With Stage I ER+ Breast Cancer: A SEER-Based Analysis - Bazan, Jose G.; Fisher, James L.; Park, Ko Un; Marcus, Elizabeth A.; Bittoni, Marisa A.; White, Julia R. (Frontiers in Oncology, 2019)
Purpose: Lumpectomy (L) and breast radiotherapy (RT) results in equivalent outcomes in comparison to mastectomy (M) for early-stage breast cancer (BC) based on randomized controlled trials (RCT). Since 2004, RCT support that L without RT yields equivalent survival and acceptable local-regional outcomes in women ≥70-years old with T1N0 hormone-sensitive (ER+) BC on endocrine therapy. Based on this, we hypothesized that M rates should decrease substantially after 2004 in this low-risk elderly population. Methods: We used the Surveillance Epidemiology and End Results registry data to conduct this study. We included women with T1N0 ER+ BC from 2000-2014. We compared M rates in women diagnosed from 2000-2004 versus 2005-2012 using the Chi-Square test. Logistic regression analyses was performed to examine demographic/clinical factors associated with mastectomy. Results: 67,506 women met the study criteria. In elderly Stage I ER+ BC, the M rate decreased by 6.3%: 29.0% before 2004 to 22.7% after 2004 (p<0.0001). M rates remained higher in elderly non-Hispanic black (NHB, 27.1%, p<.0001), non-Hispanic Asian-Pacific-Islander (NHAPI, 30.1%, p<.0001), and Hispanics (24.4%, p=.0004) vs. non-Hispanic White (NHW, 21.5%). Treatment in the modern cohort was associated with decreased odds of mastectomy (OR=0.71, 95% CI 0.68-0.74, p<.0001) while NH-API race was associated with the highest increased odds of mastectomy (OR=1.65, 95% 1.53-1.78, p<.0001). In the modern cohort specifically (2005-2014), Hispanic women (OR=1.12, p=0.014), NHB women (OR=1.21, p<0.0001), and NHAPI women (OR=1.73, p<0.0001) all had higher odds of undergoing mastectomy relative to NHW women after adjusting for all other patient and tumor related factors. Conclusions: In elderly patients with stage I, ER+ BC, M rates have decreased modestly since 2004. These trends are driven mostly be decreases in the M rate in NHW women, but M rates remain 25% in Hispanic, NHB, and NHAPI women. Further research is needed to identify why M, which is associated with higher cost and morbidity than L alone, has not changed substantially in elderly, low-risk BC.